Taurine reduces the secretion of apolipoprotein B100 and lipids in HepG2 cells - Yanagita, Teruyoshi (BioMed Central, 2008)
BACKGROUND: Higher concentrations of serum lipids and apolipoprotein B100 (apoB) are major individual risk factors of atherosclerosis and coronary heart disease. Therefore ameliorative effects of food components against the diseases are being paid attention in the affluent countries. The present study was undertaken to investigate the effect of taurine on apoB secretion and lipid metabolism in human liver model HepG2 cells. RESULTS: The results demonstrated that an addition of taurine to the culture media reduces triacylglycerol (TG)-mass in the cells and the medium. Similarly, cellular cholesterol-mass was decreased. Taurine inhibited the incorporation of [(14)C] oleate into cellular and medium TG, suggesting the inhibition of TG synthesis. In addition, taurine reduced the synthesis of cellular cholesterol ester and its secretion, suggesting the inhibition of acyl-coenzyme A:cholesterol acyltransferase activity. Furthermore, taurine reduced the secretion of apoB, which is a major protein component of very low-density lipoprotein. CONCLUSION: This is a first report to demonstrate that taurine inhibits the secretion of apoB from HepG2 cells.